Antifungal activity of ethyl acetate extract of Trichoderma harzianum against Fusarium sp. - Ayu Nawang Wulan; Tasya Umi Pertiwi; Puspita Aulia Cahyani (Jurnal Biologi Udayana, 2026)
Fusarium sp. is one of the main pathogens causing wilt disease in chili plants (Capsicum annuum L.) which can cause a significant decrease in production. Control of this disease still relies heavily on synthetic fungicides that have the potential to cause pathogen resistance and negative impacts on the environment. Therefore, an alternative biological control is needed, namely with Trichoderma harzianum. This study aims to test the antifungal activity of ethyl acetate extract of T. harzianum against Fusarium sp. in vitro. T. harzianum isolates were incubated with Potato Dextrose Broth (PDB) medium for nine days, then their secondary metabolites were extracted using ethyl acetate solvent and evaporated to obtain a crude extract. Antifungal activity was tested using the disc diffusion method against Fusarium sp. suspensions with a concentration of 1 × 10⁷ spores/mL. The treatments used included ethyl acetate extract of T. harzianum (10 mg/mL), natacen as a positive control, aquadest as a negative control, and ethyl acetate as a solvent control. The results showed that the ethyl acetate extract of T. harzianum was able to inhibit the growth of Fusarium sp. with an average inhibition zone diameter of 17 mm. Meanwhile, natacen produced an inhibition zone of 35.5 mm, while the negative control and solvent control showed no inhibitory activity. These results indicate that the secondary metabolites contained in the ethyl acetate extract of T. harzianum possess antifungal activity against Fusarium sp. and have the potential to be developed as a safer and more sustainable biological control agent..